The Visegrád countries: Coronavirus pandemic, EU transfers, and their impact on Austria - Vasily Astrov; Mario Holzner (The Vienna Institute for International Economic Studies (wiiw), 2021)
The Visegrád economies have been hit hard by the COVID-19 pandemic, especially its second wave. In response, macroeconomic policies have been markedly relaxed, with fiscal stimulus packages reaching up to 14% of GDP in Poland and Czechia. The projected recovery of the Visegrád economies from 2021 onwards should be significantly helped by the massive inflow of EU transfers, particularly from the newly established Next Generation EU recovery fund. Such transfers will boost their economies by between 2.1% per year in Slovakia and 1% in Czechia, at a minimum; the effect should be stronger once EU transfers to other member states are taken into account. The cumulative boost to the Austrian economy in 2021-2022 from EU transfers to the Visegrád countries is estimated at least at 0.12%, thus partly offsetting the net contributions paid by Austria to the EU budget (which stood at 0.31% of Austria's GNI in 2019). Given strong cross-border spillovers of fiscal policy measures and historically low interest rates, the governments of the Visegrád countries and Austria (and Germany) should be interested in a more expansionary fiscal policy at EU level for the benefit of the less-developed EU member states. In addition, greater co-ordination of national policies among the above-mentioned countries would be advisable in the planning and implementation of COVID-19 restrictions, as well as in the resolution of mass insolvencies that are likely to follow the withdrawal of large-scale fiscal stimulus measures. It might also be advisable to establish joint Central European working groups to analyse possible scenarios of the economic situation in the post-COVID world.
Keywords: F0; H30; H50; H77; 330; fiscal policy; EU transfers; fiscal multiplier; input-output tables